Structure-Based Design of 2-Aminopurine Derivatives as CDK2 Inhibitors for Triple-Negative Breast Cancer - Liang, Hanzhi; Zhu, Yue; Zhao, Zhiyuan; Du, Jintong; Yang, Xinying; Fang, Hao; Hou, Xuben (Frontiers in Pharmacology, 2022)
Cyclin-dependent kinase 2 (CDK2) regulates the progression of the cell cycle and is critically associated with tumor growth. Selective CDK2 inhibition provides a potential therapeutic benefit against certain tumors. Purines and related heterocycle (e.g., R-Roscovitine) are important scaffolds in the development of CDK inhibitors. Herein, we designed new series of 2-aminopurine derivatives based on the fragment-centric pocket mapping analysis of CDK2 crystal structure. Our results indicated that the introduction of polar substitution at the C-6 position of purine would be beneficial for CDK2 inhibition. Among them, compound 11l showed good CDK2 inhibitory activity (IC50=19 nM) and possess good selectivity against other CDKs. Further in vitro tests indicated that compound 11l possesses anti-proliferation activity in MDA-MB-231 cells. Moreover, molecular dynamics simulation suggested the favorable binding mode of compound 11l, which may serve as a new lead compound for the future development of CDK2 selective inhibitors.